"Most MPs are Not All that Sharp." Political Employees and Representative Democracy. Issue 7 (7th June 2017) - Svallfors, Stefan
ABSTRACT: The article analyses the orientations of political employees in Sweden. It finds that their roles are diffuse: there is no agreement among political employees about whether they are politicians or not, and their mandate is fleeting and unclear. They hold the average politician's intellectual abilities in low regard, and sometimes take on clearly paternalistic views toward elected representatives. They see little attraction in pursuing a career as elected politicians, because of intrusive media scrutiny and since they hold a view of elected politics as slow, boring, and shallow. The professional route to politics is seen as more fast and fun.